2011
DOI: 10.1007/s00547-002-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iloprost on blood rheology and tissue perfusion in patients with intermittent claudication: Results of a double-blind placebo-controlled study

Abstract: The eects of an infusion of a single dose of Iloprost (from 0.5 up to a maximum of 2 ng/kg/min for six hours) in patients with stage II peripheral vascular disease (PVD) on blood rheology and tissue perfusion were determined in a double-blind placebo-controlled study using repeated treadmill exercise test to stress leg circulation. Blood viscosity (BV) at low shear, soluble Pselectin levels (expression of platelet activation), unfractioned leukocyte and erythrocyte ®lterability rates (using a constant-¯ow posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The dose-response relationship in these topically administered agents was not investigated. Although iloprost has also been shown to have beneficial rheologic and cytoprotective actions when administered intravascularly, 38,39 our study focused solely on the vasodilatory properties and did not assess how these rheologic and cytoprotective actions contributed to improved flap perfusion. Our experimental design allowed analysis of necrosis only up to postoperative day 7 and did not show long-term wound healing results.…”
Section: Discussionmentioning
confidence: 99%
“…The dose-response relationship in these topically administered agents was not investigated. Although iloprost has also been shown to have beneficial rheologic and cytoprotective actions when administered intravascularly, 38,39 our study focused solely on the vasodilatory properties and did not assess how these rheologic and cytoprotective actions contributed to improved flap perfusion. Our experimental design allowed analysis of necrosis only up to postoperative day 7 and did not show long-term wound healing results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a previous study, it was shown that microvascular perfusion was improved with doses of 0.5-2 ng/kg/min (12).…”
Section: Discussionmentioning
confidence: 99%